The Development of the Visual Digital-Based Practicum Manual for Microbiology to Support Students’ Communication Skills - Risna Hani; Aminuddin Prahatama Putra; Dharmono Dharmono (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
Communication skills in a microbiology practicum can be developed by composing a practicum report and optimized by utilizing a practicum manual. The development of a practicum manual for microbiology is necessary to facilitate students' communication skills. Researchers have developed visual digital-based practicum manuals for microbiology to fulfill these needs. This research aims to describe the validity of a visual digital-based practicum manual for microbiology to support students’ communication skills. This research employed the Alessi & Trollip model. Product validity was conducted through the alpha test by involving three experts and employing expert validation instruments with non-test techniques to reveal the feasibility of material-based media visual aspects, and software engineering aspects. The results show that the media developed is completely valid on the material aspects, navigation aspects, and display aspects.